Perceptions of Community Health Center’s Workers on National Health Insurance (JKN) Healthcare Services Payment System in Karangasem Regency - Ni Wayan Ani Hendrayani; Putu Ayu Indrayathi; I Putu Ganda Wijaya (Public Health and Preventive Medicine Archive, 2015)
Background and purpose: National Health Insurance (JKN) healthcare services payment system is a financial compensation given to employees of health centers through an allocation system implemented by the Ministry of Health Regulation (Permenkes No. 28 of 2014). This study aims to explore health care workers perception of the JKN health care services payment system. Methods: In-depth interviews conducted among 12 participants selected purposively namely heads of health centers (doctors and public health graduated), medical personnel, paramedics, other health professionals, non-health personnel (both civil servants and noncivil servants). Data were analyzed using thematic analysis approach presented narratively. Results: Participants intimated that the amount of points based on the variable of kind of personnel and/or positions were not proportional/not in accordance with the actual condition of the health center. The use of attendance rates made for an unconducive atmosphere as it was evident that this variable was not applied to all employees but only to the central health centers. The differentiation of employment status with the same workload, and the uneven amount of points and grouping of years of service rather than workload was viewed as unfair and bias by respondents therefore they believed this needs further assessment. Conclusion: The allocation of the JKN health care services payment system was perceived as prejudicial by the employees of the health centers in Karangasem Regency. The amount of points distributed were not proportional to the type of personnel and/or position, and the use of the level of attendance, differentiation of employment status, grouping of years of service not based on workloads were all issues raised by respondents.